Spatio-temporal resolution of taxonomic and functional microbiome of Lonar soda lake of India reveals metabolic potential for bioremediation - Chakraborty, Jaya; Rajput, Vinay; Sapkale, Vibhavari; Kamble, Sanjay; Dharne, Mahesh (Chemosphere, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Lonar Lake, India; a hypersaline and hyperalkaline extremophilic ecosystem having a unique microbial population has been rarely explored for bioremediation aspects. MinION-based shotgun sequencing was used to comprehensively compare the microbial diversity and functional potential of xenobiotic degradation pathways with seasonal changes. Proteobacteria and Firmicutes were prevalent bacterial phyla in the pre-monsoon and post-monsoon samples. Functional analysis from SEED-subsystem and KEGG database revealed 28 subsystems and 18 metabolic pathways for the metabolism of aromatic compounds and xenobiotic biodegradation respectively. Occurrence of N-phenyl alkanoic, benzoate, biphenyl, chloroaromatic, naphthalene, and phenol degradation genes depicted varied abundance in the pre-monsoon and post-monsoon samples. Further, KEGG analysis indicated nitrotoluene degradation pathway (ko00633) abundant in post-monsoon samples, and the benzoate degradation pathway (ko00362) predominant in 19LN4S (pre-monsoon) than 18LN7S (post-monsoon) samples. The abundant genes for benzoate degradation were pcaI: 3-oxoadipate CoA-transferase, alpha subunit, pcaH: protocatechuate 3,4-dioxygenase, beta subunit, and pcaB: 3-carboxy-cis, cis-muconate cycloisomerase, and 4-oxalocrotonate tautomerase. This metagenomic study provides a unique blueprint of hitherto unexplored xenobiotic biodegradation genes/pathways in terms of seasonal variations in the Lonar Lake, and warrants active exploitation of microbes for bioremediation purposes.